Performance prediction and evaluation of the scroll-type hydrogen pump for FCVs based on CFD–Taguchi method. (7th June 2019) - Zhang, Qingqing; Feng, Jianmei; Zhang, Quanquan; Peng, Xueyuan
Abstract: To improve hydrogen utilisation and provide superior water management, the recirculation hydrogen pump is one of the key components in a fuel-cell vehicle (FCV). This work focused on the performance estimation of a scroll-type hydrogen pump for FCVs. A series of CFD simulation cases were designed using the Taguchi method and were carried out to determine the optimum conditions for volumetric efficiency, and the effects of four factors, including pressure ratio, rotating speed, axial clearance, and radial clearance. The contributions of these factors on volumetric efficiency and shaft power were quantified by the analysis of variance (ANOVA) method. The results show that axial clearance and rotating speed are the main influencing factors on volumetric efficiency, and their contribution ratios are 45.3% and 39.6%, respectively, in the operational range of the hydrogen pump for FCVs. Pressure ratio and rotating speed should be considered first to reduce shaft power, and their contribution ratios are 40.9% and 55.4%, respectively. At last, the performance maps of the scroll-type hydrogen pump were obtained to reveal the dynamic changes at various working conditions. It is found that volumetric efficiency and shaft power are more sensitive to the change in rotating speed when the pressure ratio deviates from the designed value. The results can be used as guidelines for component matching in the design and operation of PEM fuel cell systems. Graphical abstract: Description of the Graphical Abstract: CFD-Taguchi method was applied to optimize the design of a scroll-type hydrogen pump with low power consumption, high efficiency for FCVs. 16 cases based on orthogonal array were carried out instead of 256 cases to gain the performance of the pump influenced by four factors, including pressure ratio, rotating speed, axial clearance, and radial clearance. Image 1 Highlights: A series of CFD simulation cases were designed using the Taguchi method. The contributions on volumetric efficiency and shaft power were quantified by the ANOVA method. The performance maps of the scroll-type hydrogen pump were evaluated.